Design, Synthesis, Antihyperglycemic Studies, and Docking Simulations of Benzimidazole-Thiazolidinedione Hybrids - Abraham Gutierréz-Hernández; Yelzyn Galván-Ciprés; Elix Alberto Domínguez-Mendoza; Yoshajandith Aguirre-Vidal; Samuel Estrada-Soto; Julio César Almanza-Pérez; Gabriel Navarrete-Vázquez (Journal of Chemistry)
A simple and cheap three-step procedure for the synthesis of three (5Z)-5-[3(4)-(1H-benzimidazol-2-ylmethoxy)benzylidene]-1,3-thiazolidine-2,4-diones has been described via a SN2 reaction of generally recognized as safe hydroxybenzaldehydes and 2-(chloromethyl)-1H-benzimidazole, followed by a Knoevenagel condensation with thiazolidine-2,4-dione in moderated yields. All the newly synthesized compounds were characterized using analytical and spectral studies. In vitro treatment on adipocytes with compounds increased the mRNA expression of two proteins recognized as strategic targets in diabetes: PPARγ and GLUT-4. In silico studies were conducted in order to explain the interaction binding mode of the synthesized compounds on PPARγ. In vivo studies confirmed that compounds 1–3 have robust antihyperglycemic action linked to insulin sensitization mechanisms. The present study provides three compounds with a promising antidiabetic action.